Edukasi Posisi Kerja Ergonomis untuk Mengurangi Risiko Low Back Pain pada Pekerja UMKM Rania Cake and Cookies di Kota Ponorogo - Nurul Hidayati, Kunti Aisyah; Bayu Prastowo (Rena Cipta Mandiri, 2025)
Low back pain (LBP) is a common musculoskeletal disorder that often occurs due to excessive muscle contraction. It may also be caused by heavy workloads and long working hours. Workers across various sectors generally experience LBP and can interfere with daily activities. Understanding preventive measures for LBP is crucial to reduce its occurrence. This community service activity aimed to provide education to workers regarding LBP, including its definition, causes, risk factors, ergonomic working positions, and stretching exercises as preventive strategies. The program was implemented using the Participatory Education Method (PEM) approach. The activities were carried out through poster media, interactive discussions in the form of question-and-answer sessions to identify workers’ problems, and simulations of stretching exercises that can be practiced during work breaks. The results showed a significant increase in workers’ knowledge about LBP. This improvement in understanding is expected to raise workers’ awareness of maintaining ergonomic posture and performing regular stretching exercises, thereby reducing the incidence of LBP in the workplace.